Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education

Learning to Plan by Learning to Reflect?—Exploring Relations between Professional Knowledge, Reflection Skills, and Planning Skills of Preservice Physics Teachers in a One-Semester Field Experience - Vogelsang, Christoph; Kulgemeyer, Christoph; Riese, Josef (Education Sciences)
Following concepts describing lesson planning as a form of anticipatory reflection, preservice physics teachers’ reflection skills are assumed to be positively connected with their planning skills. However, empirical evidence on this is scarce. To explore how relations between these specific skills change over the course of a field experience controlling for influences of professional knowledge, we conduct a pre-post field study with N = 95 preservice physics teachers in a one-semester field experience. Content knowledge (CK) and pedagogical content knowledge (PCK) (paper-and-pencil tests), and reflection and planning skills (standardized performance assessments) were assessed before and after the field experience. Path analyses revealed almost no influence of reflection skills on planning skills. Reflections skills did not contribute to preservice teachers planning skills beyond knowledge, indicating both constructs might represent rather independent abilities. The results show the need for further development of models describing the development of teachers’ professional knowledge and skills in academic teacher education and for the development of concepts for a better integration of reflection and lesson planning in field experiences.
Keywords: Public Administration; Developmental and Educational Psychology; Education; Computer Science Applications; Computer Science (miscellaneous); Physical Therapy; Sports Therapy and Rehabilitation

Exploring the effects of physics explainer videos and written explanations on declarative knowledge and the illusion of understanding - Kulgemeyer, Christoph; Hörnlein, Madeleine; Sterzing, Fabian (International Journal of Science Education)
Keywords: Education

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Comparing tablet and print mode of a german reading comprehension test in grade 3: Influence of test order, gender and language - Seifert, Susanne; Paleczek, Lisa (International Journal of Educational Research)
Keywords: Education

Bending and Bowing: How Teachers Adapt a Vocabulary-Based Reading Program to Their Students Needs - Kulmhofer-Bommer, Andrea; Seifert, Susanne; Paleczek, Lisa; Gasteiger-Klicpera, Barbara (Journal of Education)
This paper investigates the implementation of a reading program designed for third grade elementary school classrooms in Austria. Using a mixed-methods approach, lesson types were identified, respective class compositions analyzed, and the effects on students’ reading gains examined. The results show that the lesson types seem to reflect learner group needs as students in the different lesson types profited similarly from the reading program. This supports the hypothesis that reading is a highly individualized process and leads to the conclusion that the instructional approach of the reading program investigated supports teachers in conducting reading lessons tailored to their students’ needs.
Keywords: Education

A feasibility study of digital content use in inclusive, Austrian primary school practice - Paleczek, Lisa; Ender, Daniela; Berger, Jessica; Prinz, Katharina; Seifert, Susanne (International Journal of Educational Research)
Keywords: Education

First-year university students' self-regulated learning during the COVID-19 pandemic: a qualitative longitudinal study - Liebendörfer, Michael; Kempen, Leander; Schukajlow, Stanislaw (ZDM – Mathematics Education)
Abstract When the COVID-19 pandemic began, many universities switched to fully online teaching. This unexpected switching to online teaching was challenging for both teachers and students, and restrictions that were put in place because of pandemic made this challenge even greater. However, new ways of teaching might also open new opportunities for students’ learning. The research question driving our study was as follows: how do students regulate their learning and specifically their choice of resources and peer learning in university mathematics classes that are fully taught online as offered during the COVID-19 pandemic? We report on a longitudinal, qualitative study in which students recorded a brief audio diary twice a week over one whole semester (14 weeks). We focused on three students who completed 70 interviews in total and finished the semester with varying degrees of success. The results show how the students structured their studying (e.g., the roles that deadlines or synchronous teaching events played). They illustrate the strengths and limitations of digital materials provided by the lecturer and the use of complementary media. Further, the pandemic uncovered the double-edged role of simple, often anonymous exchanges (e.g., via Discord servers), with few binding forces for either side, and the significance of stable learning partnerships for students’ success. Our research highlights aspects that should be focal points when comparing traditional instruction and online instruction during the pandemic from a self-regulatory perspective. Practical implications refer to how these aspects can be combined sensibly in fully online courses, but also in blended learning contexts.
Keywords: General Mathematics; Education

Exploring the Perceived Relevance of University Mathematics Studies by First-Semester Teaching Students - Büdenbender-Kuklinski, Christiane; Hochmuth, Reinhard; Liebendörfer, Michael (International Journal of Research in Undergraduate Mathematics Education)
Abstract As earlier research results suggest that many mathematics teaching students criticize a missing relevance in their studies, we explore explanations and interrelationships of their relevance assessments. We aim at finding out how one could support the students in attributing relevance to their study programs. A two-fold model for relevance assessments in mathematics teacher education is proposed, consisting of relevance content and relevance reasons. We investigate students' relevance perceptions of mathematical topics and of topics’ complexities, as well as their rating of individual and societal/ vocational relevance reasons, all in relation to their perception of the relevance of their overall program of study. Contrary to earlier research findings, our results suggest that mathematics teaching students already do attribute relevance to many content areas and that a preparation for the teaching profession is not the only reason for them to assign relevance. There also seem to be many students who would attribute relevance if they could develop as individuals and pursue their interests. We suggest that giving students opportunities to set individual priorities in their studies could hence support their relevance assessments. As low relevance assessments seem to be connected to students’ motivational problems, students might profit from motivational support, as well.
Keywords: Education; Mathematics (miscellaneous)

Messung von Unterrichtsplanungskompetenz im Fach Sachunterricht: Empirische Befunde zur Kompetenzentwicklung angehender Grundschullehrkräfte auf Grundlage einer mehrdimensionalen Kompetenzstruktur - Kirsch, Alexander (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im vorliegenden Beitrag werden nach ausführlicher theoretischer Diskussion des Kompetenzbegriffs und der Definition von Kompetenz als Können ein Modell sachunterrichtlicher Planungskompetenz sowie ein daran anschließendes Messinstrument vorgestellt. Im Hinblick auf den Einsatz dieses Instrumentes im Rahmen einer Evaluation des nordrhein-westfälischen Praxissemesters stellen sich Fragen nach der psychometrischen Struktur der Testauswertung. Da das Instrument sowohl zur Testung von Sachunterrichtsstudierenden mit dem Lehramtsprofil ‚Grundschule‘ als auch von Sachunterrichtsstudierenden mit sonderpädagogischem Schwerpunkt eingesetzt werden soll, ist zu zeigen, dass die Testergebnisse nicht durch den gewählten Studiengang beeinflusst werden. Im Beitrag werden Rohdaten aus einer Studie an der Universität Paderborn ( n = 121) genutzt, um eine fünfdimensionale Modellstruktur gegen eine eindimensionale zu testen und empirisch gestützte Argumente für eine mehrdimensionale Skalierung zu generieren. Durch Differential-Item-Functioning-Analysen wird geprüft, ob die Itemschwierigkeiten mit dem Merkmal ‚Studiengang‘ interagieren, sodass sie sich trotz gleicher Kompetenzausprägung für Untersuchungsteilnehmende beider Studierendengruppen signifikant unterscheiden und zu einer diagnostischen Verzerrung führen würden. Abschließend wird der beispielhafte Einsatz des Instrumentes im Rahmen einer Wirksamkeitsanalyse in Bezug die Effektivität des nordrhein-westfälischen Praxissemesters an der Universität Paderborn ( n = 26) dargelegt. Aus den differenzierten Ergebnissen werden unter anderem erste Hinweise auf Defizite in der Lehrerinnen- und Lehrerausbildung abgeleitet.
Keywords: Education

Entwicklung und Evaluation eines Fortbildungskonzepts im Kontext der technischen Bildung an Grundschulen am Beispiel von Lernrobotern - Janicki, Nicole (Technik: Verstehen wir, was wir nutzen!? - Tagungsband zur 23. Jahrestagung der Deutschen Gesellschaft für Technische Bildung in Mannheim vom 24.-25. September 2021.)
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots

The role of ICT for school leadership and management activities: an international comparison - Tulowitzki, Pierre; Gerick, Julia; Eickelmann, Birgit (International Journal of Educational Management)
Purpose Information and communication technologies (ICT) has an increasing impact on schools. School leaders play a key role in this context as drivers of innovation including those related to ICT. Against this background, the study presented in this article focuses on school leadership and management activities with ICT and related challenges. It sought to analyze how frequently German school principals use ICT compared to principals in other countries, what distinct clusters of German principals could be identified in terms of ICT usage and how principals viewed ICT in schools and related challenges. Design/methodology/approach A mixed-methods approach was chosen, using quantitative data from both the international comparative large-scale assessment study ICILS 2018 and the explorative qualitative data from Germany. For the international comparison, the school principal data sets of the 12 international participants of the International Computer and Information Literacy Study (ICILS) 2018 were taken into account: Chile, Denmark, Finland, France, Germany, Italy, Kazakhstan, Republic of Korea, Luxembourg, Portugal, Uruguay and the United States. To look beyond averaged frequencies, a latent class analysis (LCA) was conducted to identify possible clusters of school leaders with distinct usage patterns of ICT for leadership and management activities. Findings The results indicate that, in general, German principals use ICT for leadership and management activities on a similar level as their international colleagues. However, they seem to communicate with education authorities significantly more often than their international colleagues, whereas representative activities (presentations, home page) are rather infrequent. The qualitative data point to significant barriers to fully harnessing the potential of using ICT for leadership, management and school improvement such as lack of competencies and lack of adequate support. Originality/value To the best of the authors’ knowledge, this is the first study that focuses on school leadership and management activities using ICT with such a data set. The results provide insights into how German principals use ICT to lead and manage their schools compared to their international counterparts. The qualitative data offers additional insights into possible reasons hindering a more effective use of ICT.
Keywords: Organizational Behavior and Human Resource Management; Education; Organizational Behavior and Human Resource Management; Education

Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education

Development and validation of a video-based test instrument to measure noticing with regard to processes ofrecognition in inclusive physical education - Langer, Wiebke; Bruns, Julia; Erhorn, Jan (German Journal of Exercise and Sport Research)
The construct of noticing is considered to be of crucial importance for professional action of (prospective) physical education (PE) teachers in the context of (inclusive) PE. In order to implement the demands of inclusive PE teaching, noticingwith regard to processes of recognition proves to be particularly significant. Due to the relevance of physicality, the design of recognition relationships that encourage pupils' development results in specific requirements for the selective attention and the theory-based interpretation of processes of recognition and disregard in complex teaching situations. This facet of competence has hardly been studied so far, partly due to the lack of instruments for standardised assessment of this construct. In the context of this paper, the development and validation of a standardised, video vignette-based test instrument for the measurement of noticingwith regard to processes of recognition of prospective PE teachers is presented. The validation focuses on the content of the test and the internal structure of the instrument as well as on correlations with related constructs in terms of content. The results from three consecutive validation studies provide indications of the reliability and validity of the test score interpretation of the instrument ViProQiS_A. The findings so far indicate that the standardised measurement of noticingwith regard to processes of recognitionin inclusive PE could be realized on the basis of the test instrument developed here.
Keywords: Physical education teacher education; Competence modelling and; measurement; Inclusive physical education; Video-based items; Noticing

Einfluss der Berufserfahrung von Multiplikatorinnen und Multiplikatoren auf die Wirksamkeit von Fortbildungsmaßnahmen zur frühen mathematischen Bildung. Zeitschrift Für Erziehungswissenschaft - Hagena, Maike; Bruns, Julia; Gasteiger, Hedwig (Zeitschrift für Erziehungswissenschaft)
Teachers expect facilitators to have own teaching experience as a teacher in order to be able to carry out effective teacher professional development programs. As part of the project EmMa(M), it is investigated, to which extent the teaching experience of facilitators influences the development of early childhood teachers' (n = 83) mathematical pedagogical content knowledge (MPCK) and early childhood teachers' enjoyment of mathematics in the context of a teacher professional development program. It turns out that the teaching experience of the facilitators has no influence on the development of early childhood teachers' MPCK, but favors the development of early childhood teachers' enjoyment of mathematics. Controlling for this increased enjoyment an influence of teaching experience on the development of early childhood teachers' MPCK emerges, but in favor of the participating facilitators who have no teaching experience but have a university degree.
Keywords: Facilitator professional development; Early childhood teachers; Teaching; experience; Early mathematics education

Labor market spillover effects of a compulsory schooling reform in Germany - Schiele, Valentin
Compulsory schooling reforms are often used to estimate monetary returns to education. Such reforms are unrelated to individual characteristics and preferences and thus arguably able to eliminate selection bias. However, as these reforms affect a large number of individuals in the relevant age groups, they might have spillover effects on individuals not directly affected by the reform. Such spillover effects constitute a problem for identification and estimation of returns to schooling. As they are difficult to address, they are mostly ignored in the empirical literature. I show that the introduction of the compulsory ninth grade in Germany led to a labor supply shock that might have increased wages and employment of individuals who were not directly subject to the reform and were assumed not to be affected in previous research. To investigate in this kinds of spillover effects, I exploit the staggered introduction of the compulsory ninth grade across German federal states in a difference-in-differences approach. Based on large scale register and survey data, I find no evidence for persistent spillover effects for men. For women, however, my results suggest that the labor supply shock resulting from the reform may have led to a persistent increase in employment and wages.
Keywords: Compulsory schooling; Education; Spillover effects; Cohort size; Wages; Employment

Group work and student procrastination - Koppenborg, Markus; Klingsieck, Katrin B. (Learning and Individual Differences)
Keywords: Developmental and Educational Psychology; Education; Social Psychology

A PLACE FOR A DATA SCIENCE PROJECT IN SCHOOL: BETWEEN STATISTICS AND EPISTEMIC PROGRAMMING - PODWORNY, SUSANNE; HÜSING, SVEN; SCHULTE, CARSTEN (STATISTICS EDUCATION RESEARCH JOURNAL)
Aspects of data science surround us in many contexts, for example regarding climate change, air pollution, and other environmental issues. To open the “data-science-black-box” for lower secondary school students we developed a data science project focussing on the analysis of self-collected environmental data. We embed this project in computer science education, which enables us to use a new knowledge-based programming approach for the data analysis within Jupyter Notebooks and the programming language Python. In this paper, we evaluate the second cycle of this project which took place in a ninth-grade computer science class. In particular, we present how the students coped with the professional tool of Jupyter Notebooks for doing statistical investigations and which insights they gained.
Keywords: Education; Statistics and Probability

Wait-and-see-ism as partial adoption of management practices: The rise and stall of integrated reporting - Endenich, Christoph; Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Strategic Organization)
Integrated reporting has widely been promoted as the next evolutionary step in corporate disclosure, which would soon replace traditional reporting practices. Embedded in a zeitgeist that favors sustainability, this outlook would suggest high integrated reporting adoption rates among reporting organizations. Our analysis of integrated reporting in Germany from 2008 to 2019 shows, however, that organizations approached integrated reporting with a wait-and-see mentality. This approach cannot be described adequately by the existing conceptualizations of (partial) practice adoption. We therefore develop the notion of wait-and-see-ism, defined as the deliberate and potentially long-lasting postponement of a decision to adopt a practice while its further development is monitored silently. We see limited, though continuous, efforts to prepare for the prospect of adopting the practice of integrated reporting quickly at a later stage. Wait-and-see-ism expands on prior work on partial adoption by emphasizing its temporal dimension. This adds an important yet undertheorized option that organizations can employ to respond to ambiguous institutional demands, thus explaining the stalling of promising management practices.
Keywords: Strategy and Management; Industrial relations; Education; Business and International Management

Prospective Teachers’ Diagnostic Thinking on Students’ Understanding of Multi-Digit Multiplication: A Content-Related Analysis on Unpacking of Knowledge Elements - Dröse, Jennifer; Prediger, Susanne (Journal für Mathematik-Didaktik)
Abstract Teachers’ in-depth diagnostic thinking has been shown to be crucial for student-centered teaching as they need to perceive and interpret students’ understanding for well-informed decision-making on adaptive teaching practices. The paper presents a content-related approach to analyzing diagnostic thinking processes with respect to the mathematical knowledge elements that prospective teachers identify as students’ resources and obstacles. Prospective teachers’ challenge is that some relevant knowledge elements first have to be unpacked, because compact concepts (such as the place value concept) or procedures (such as for multi-digit multiplication) comprise several smaller knowledge elements (such as the positional property) that have to be made explicit for students to foster their learning processes adequately. Our study examines what knowledge elements prospective teachers perceive and interpret in a transcript vignettes on multi-digit multiplication (of decimal and natural numbers) and its underlying basic arithmetic concepts (place value understanding and meaning of multiplication) in written diagnostic judgments on students’ resources and obstacles ( N = 196). A comparative design within the vignette is used to investigate how far the process of perceiving can be supported by thematic cues. The analysis reveals that those knowledge elements cued in the vignette by being already unpacked and explicitly addressed are perceived and interpreted more often (but with lower correctness) than those that are uncued and therefore have to be unpacked by the prospective teachers themselves. This confirms the need to prepare prospective teachers for unpacking mathematical concepts themselves.
Keywords: Education; General Mathematics

Organisation der dualen Berufsausbildung zum/zur Verkäufer:in und Kaufmann:frau im Einzelhandel im Zeichen der COVID-19-Pandemie. - Sommer, Christian; Szczesny, Daniela (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern.)
One of the most powerful events in the still young 21st century is certainly the outbreak of the coronavirus and the following COVID-19 pandemic. Massive economic as well as social distress caused worldwide devastation. In Germany, not only stores, factories, cultural facilities were closed, but also – for the first time in history – schools were closed nationwide. Closed working sites and vocational schools, as well as working sites, which remained open due to their systemic relevance, led to so far unknown challenges in Germany’s vocational education system. A very good example are the dual apprenticeships, such as trained retail salesman, which were only partially affected by closures. The main goal of education policy was to compensate personal communication and interaction via digital media. This article’s main aim is to reveal the strategies vocational schools have developed to overcome the challenges they had to face because of the pandemic.
Keywords: COVID-19; Digitalization; Vocational education and training; Retail

Ein kritisch-multiperspektivischer Blick auf Forschendes Lernen in der Lehrkräftebildung - Bloh, Thiemo; Caruso, Carina (die hochschullehre)
Forschendes Lernen in der Lehrer:innenbildung ist seit der Ausweitung schulpraktischer Anteile bzw. der Einführung des sogenannten Praxissemesters eng verwoben mit der Lehrer:innenausbildung. Gleichzeitig wird bisher weitestgehend different beantwortet, was Forschendes Lernen ist und sein kann sowie warum es wie hochschuldidaktisch gerahmt wird und werden sollte. Der Beitrag widmet sich dieser Frage. Dabei zeigt sich einerseits, dass hochschuldidaktische Zugänge zur Realisierung Forschenden Lernens in der Lehrer:innenbildung erst vor dem Hintergrund theoretischer Annahmen zur Entwicklung von Lehrpersonen und deren Professionalität sowie zur Gestalt - gemeint ist hier der Beitrag zu dieser Entwicklung sowie der Anteil an Professionalität - Forschenden Lernens entwickelt werden können, eine solche Fundierung aber oftmals ausbleibt. Andererseits wird herausgearbeitet, inwiefern eine Differenz zwischen wissenschaftlicher Forschung und Forschung im Forschenden Lernen besteht. Daran anschließend wird eine habitustheoretische Fundierung Forschenden Lernens vorgestellt und es werden exemplarisch deren Implikationen für die Gestaltung Forschenden Lernens benannt. Abschließend wird anhand empirischer Rekonstruktionen beispielhaft eine praktische Umsetzung diskutiert.
Keywords: Forschendes Lernen; Lehrer:innenausbildung; Praxissemester; Professionalisierung / Research-based learning; teacher education; internships; professionalization

Scaffolding Close Reading of Mathematical Text in Pre-service Primary Teacher Education at the Tertiary Level: Design and Evaluation - Rezat, Sebastian; Malik, Sara Naseem; Leifeld, Markus (International Journal of Science and Mathematics Education)
Abstract Even in the digital age, learning mathematics at an academic level still requires much reading of mathematical text. Research has shown that reading mathematical text requires readers to engage with all the structures of the book and with its pedagogical voice, making connections, and plausible reasoning. Specific practices and strategies that support the close reading of mathematical text have been suggested; however, descriptions and empirical evaluations of materials designed to support these activities are rare. We present the design and first evaluation cycle of materials developed in a design research project that aims to scaffold close reading of mathematical text. The materials were designed and evaluated in a German university course on elementary geometry for first-year teacher education students who study mathematics to become primary teachers. The reading strategies were explained and modeled for students in reading-strategy videos. Additionally, close reading of mathematical text was scaffolded by close-reading tasks and homework tasks and problems that build on the reading strategies and were specifically designed to foster understanding of the mathematical text. Survey data were collected from 296 students to evaluate their use of and attitude toward the different materials. The quantitative results indicate that students used the materials and were generally able to learn the course content by themselves. From all provided materials, they found the close-reading tasks most helpful. A qualitative analysis of answers to open questions revealed issues with different materials, particularly with the script, and requests for additional materials. The issues with the script were categorized inductively. The categories are presented as a qualitative result of the study and discussed.
Keywords: General Mathematics; Education

Editorial: Research on Data Science Education - Biehler, Rolf; De Veaux, Richard; Engel, Joachim; Kazak, Sibel; Frischemeier, Daniel (Statistics Education Research Journal)
A very warm welcome to this Special Issue of the Statistics Education Research Journal (SERJ) on data science education. Our hope is to give an overview of selected theoretical thoughts and empirical studies on data science education from a statistics education research perspective. Data science education is rapidly developing but research into data science education is still in its infancy. The current issue presents a snapshot of this developing field.
Keywords: Education; Statistics and Probability

Teaching and Learning Data-Driven Machine Learning with Educationally Designed Jupyter Notebooks - Fleischer, Yannik; Biehler, Rolf; Schulte, Carsten (Statistics Education Research Journal)
This study examines modelling with machine learning. In the context of a yearlong data science course, the study explores how upper secondary students apply machine learning with Jupyter Notebooks and document the modelling process as a computational essay incorporating the different steps of the CRISP-DM cycle. The students’ work is based on a teaching module about decision trees in machine learning and a worked example of such a modelling process. The study outlines the students’ performance in carrying out the machine learning technically and reasoning about bias in the data, different data preparation steps, the application context, and the resulting decision model. Furthermore, the context of the study and the theoretical backgrounds are presented.
Keywords: Education; Statistics and Probability

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Developing and Evaluating the Concept Data Awareness for K12 Computing Education - Höper, Lukas (21st Koli Calling International Conference on Computing Education Research)
Students often have a lack of understanding and awareness of where, how, and why personal data about them is collected and processed. Especially, when interacting with data-driven digital artifacts, an appropriate perception of the data collection and processing is necessary for self-determination. This dissertation deals with the development and evaluation of a concept called data awareness which aims to foster students’ self-determination interacting with data-driven digital artifacts.
Keywords: data awareness; machine learning; data science education; data-driven digital artifacts; artificial intelligence

Computers and Education – Recognising Opportunities and Managing Challenges - Passey, Don; Brinda, Torsten; Cornu, Bernard; Holvikivi, Jaana; Lewin, Cathy; Magenheim, Johannes; Morel, Raymond; Osorio, Javier; Tatnall, Arthur; Thompson, Barrie; Webb, Mary (Advancing Research in Information and Communication Technology)
Keywords: Educational technologies; Education and technologies; Digital technologies and education; Information technologies; Communication technologies; Educational technologies and research; Educational technologies and pedagogical practices; Educational technologies and policy; Educational management and technologies; Professional development and educational technologies

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years.Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Education

Berufswahlmotivation angehender Wirtschaftspädagog*innen: Validierung des FIT-Choice-Ansatzes und Exploration der Gründe für das Studium der Wirtschaftspädagogik - Goller, Michael; Ziegler, Simone (Zeitschrift für Berufsund Wirtschaftspädagogik)
National und international ist in den letzten Jahren ein vergrößertes Interesse an der Erforschung der Berufswahlmotivation von Studierenden des allgemeinen Lehramtes zu beobachten. Auch in der Wirtschaftspädagogik hat die empirische Auseinandersetzung mit den Beweggründen der Studien- und Berufswahl eine gewisse Tradition. Gleichzeitig muss bemängelt werden, dass die existierenden Untersuchungen einerseits bisher keine an die nationale und internationale Forschung anschlussfähigen Erhebungsinstrumente benutzten und andererseits regional nur einzelne Hochschulstandorte berücksichtigten. Die hier berichtete Studie nimmt sich dieses Forschungsdesiderates an. Hierzu wurden 879 Studierende der Wirtschaftspädagogik an zwölf deutschen Studienstandorten mit einem standardisierten Fragebogen, basierend auf dem bereits gut etablierten FIT-Choice-Ansatz, befragt. Auf Basis dieser Stichprobe werden folgende Forschungsfragen beantwortet: (1) Inwiefern eignet sich das FIT-Choice-Instrumentarium auch für Untersuchungen von Studierenden der Wirtschaftspädagogik?, (2) Welche Motive sowie Vorstellungen vom späteren Beruf liegen der Berufswahl der befragten Studierenden der Wirtschaftspädagogik zugrunde? und (3) Inwiefern unterscheiden sich die Berufswahlmotive sowie die Vorstellungen des späteren Berufs der befragten Wirtschaftspädagogikstudierenden in Hinblick auf das Geschlecht, eine vorherige Berufsausbildung sowie den späteren Berufswunsch? Die Validierung zeigt, dass sich der FIT-Choice-Ansatz größtenteils gut eignet, um auch Studierende der Wirtschaftspädagogik zu untersuchen. Darüber hinaus geben die Befunde vertiefte Einblicke in die Berufswahlmotivation angehender Wirtschaftspädagog*innen (z. B. hohe Relevanz des polyvalenten Studiencharakters).
Keywords: Berufswahl; Motivation; Wirtschaftspädagogik; Berufliche Bildung; FIT-Choice; Lehramt; Career Choice; Business; Education; VET; FIT-Choice; Teacher Education

Have Academics’ Citation Patterns Changed in Response to the Rise of World University Rankings? A Test Using First-Citation Speeds - Lee, Soo Jeung; Schneijderberg, Christian; Kim, Yangson; Steinhardt, Isabel (Sustainability)
Academics may actively respond to the expectations of the academic status market, which have largely been shaped by the World University Rankings (WURs). This study empirically examines how academics’ citation patterns have changed in response to the rise of an “evaluation environment” in academia. We regard the WURs to be a macro-level trigger for cementing a bibliometric-based evaluation environment in academia. Our analyses of citation patterns in papers published in two higher education journals explicitly considered three distinct periods: the pre-WURs (1990–2003), the period of WURs implementation (2004–2010), and the period of adaption to WURs (2011–2017). We applied the nonparametric Kaplan–Meier method to compare first-citation speeds of papers published across the three periods. We found that not only has first-citation speed become faster, but first-citation probability has also increased following the emergence of the WURs. Applying Cox proportional hazard models to first-citation probabilities, we identified journal impact factors and third-party funding as factors influencing first-citation probability, while other author- and paper-related factors showed limited effects. We also found that the general effects of different factors on first-citation speeds have changed with the emergence of the WURs. The findings expand our understanding of the citation patterns of academics in the rise of WURs and provide practical grounds for research policy as well as higher education policy.
Keywords: world university rankings; citation; first-citation speed; Minerva; Studies in Higher Education

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years. Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Work-Based Learning; Organisational Change; Digital Competences; Qualitative Research; Digitalisation; Farming; Dairy; VET; Vocational Education and Training

Das Praxissemester aus der Perspektive von Mentor*innen: Aufgaben der Lernorte und wahrgenommene Veränderungsbedarfe - Caruso, Carina; Goller, Michael (Lehrerbildung auf dem Prüfstand)
Mentor*innen unterstützen Studierende u.a. bei der Planung, Durchführung und Reflexion von Unterricht. Obwohl Mentor*innen ein hoher Einfluss auf die Professionalisierung angehender Lehrkräfte zugeschrieben wird, gibt es nur wenige Studien, in denen die Perspektive von Mentor*innen beforscht wird. Dieser Beitrag zielt darauf, die Perspektive von Mentor*innen zu den Aufgaben der am Praxissemester beteiligten Lernorte sowie Veränderungsbedarfe zu explorieren. Hierzu werden Ergebnisse einer Interviewstudie mit 23 Mentor*innen vorgestellt, die zur Beantwortung nachstehender Forschungsfragen beitragen: (1) Welche Aufgaben haben die am Praxissemester beteiligten Lernorte und die dort tätigen Akteur*innen hinsichtlich der Vorbereitung, Unterstützung und Begleitung der Studierenden im Praxissemester aus Perspektive befragter Mentor*innen? (2) Was sind aus Sicht von Mentor*innen Veränderungsbedarfe hinsichtlich der Rahmenbedingungen bzw. Konzeption des Praxissemesters? Ein zentraler Befund der Studie ist, dass allen Lernorten attribuiert wird, dass diese Studierende auf die praktische Unterrichtstätigkeit vorbereiten sollen. Die Relevanz der Universitäten wird dabei allerdings als gering eingeschätzt. Auch theoretisch-reflexive Aspekte spielen in den Aussagen der meisten Mentor*innen keine Rolle. Veränderungsbedarf wird von den Mentor*innen vor allem in der Rolle des Zentrums für schulpraktische Lehrerausbildung und der Universität gesehen. Diese Befunde werden anschließend kritisch diskutiert.
Keywords: Lehrerbildung; Mentoring; Praxissemester; Professionalisierung / internship; mentoring; professionalisation; teacher education

Zur Relevanz von Fallarbeit - Caruso, Carina; Woppowa, Jan (Religionspädagogische Beiträge. Journal for Religion in Education)
Der Beitrag verbindet die Sichtweisen verschiedener Professionalisierungsansätze mit der Frage nach der Gestaltung der (universitären) Begleitung angehender Lehrkräfte im Praxissemester. Dabei wird der Wert von Fallarbeit herausgearbeitet und beschrieben, wie eine Unterstützung angehender (Religions-)Lehrkräfte gestaltet sein müsste, um Entwicklung und Lernen im Praxissemester systematisch zu begleiten. Der Beitrag widmet sich daher zuerst den Rahmenbedingungen und Forschungsbefunden zu Langzeitpraktika und der Gestalt von Professionalisierung durch Praxis. Daran schließen sich Denkfiguren zur Unterstützung (religionspädagogischer) Professionalisierungsprozesse von angehenden Lehrkräften im Schulpraktikum durch rekonstruktive Fallarbeit an, aus Sicht etablierter Professionalisierungsansätze.
Keywords: Fallarbeit; Praxissemester; Professionalität; Professionalisierung; Lehrerinnen- und Lehrerbildung / casework; teacher education; internship; professionalization; professionalism

Exploring the impact of pre-service science teachers’ reflection skills on the development of professional knowledge during a field experience - Kulgemeyer, Christoph; Kempin, Maren; Weißbach, Anna; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (International Journal of Science Education)
Keywords: Education

Students in the spotlight: Using collaborative autoethnography to build a community of learning in the Corona crisis - Steinhardt, Isabel (ISA Pedagogy Series)
Due to the Corona crisis, German Higher Education Institutions had to close their campuses in March and lecturers had to teach online. To understand how the Corona crisis affected students, first this article explains the structural and social inequalities in the German higher education system, using Tinto's (1975; 1997) student engagement theory. Second, the concept of Bergman-Rosamond et al. (2020) is used to analyze the challenges that Corona has raised for students, including current surveys. We found that the closure of the social space campus (and the Corona crisis as a whole) particularly hit hard those students who had previously been affected by (intersectional) inequality. Therefore, to lessen the specific challenges associated with the ad hoc transition to digital studying, the creation of a digital community of learning can help. We demonstrate how such a community can be created by the example seminar, "Digital practices: an autoethnographic observation". During the seminar, students recorded their digital technology use in a journal, and we analyzed the diary entries using the collaborate autoethnography method. The seminar example shows that this method is well suited for the development of a community of learning as it not only places students in the spotlight but as students work together on a topic they get to know each other, and a basis of trust is created through peer-feedback. Therefore, it was important to have a digital space (in this case Mahara) where the exchange could take place. The continuous insight into the students’ "learning status" enabled the lecturer to promote the learning and provide individual assistance for the students.
Keywords: Intersectionality; inequality; gender; diversity; higher-education; crisis

Kompetenzdiagnose in der Berufsbildung von Pflegelehrpersonen - Schürmann, Mirko; Bender, Elena; Grebe, Christian (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))
Zusammenfassung In diesem Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) wird das Instrument zur Diagnose pädagogischer Kompetenzen von Pflegelehrpersonen (PädKomPflege) vorgestellt. Die Berufsbildung in der Pflege ist durch sich verändernde inhaltliche und gesetzliche Anforderungen geprägt. Verschiedene landesspezifische rechtliche Vorgaben führen zu einem sehr heterogenen Bild von Qualifikationen und Kompetenzen der Pflegelehrpersonen. Die Anrechnung bereits erworbener Kompetenzen auf pflegepädagogische Studiengänge sowie die Kompetenzerfassung und -bilanzierung in Berufsbildungseinrichtungen spielt daher eine wichtige Rolle. Vor diesem Hintergrund wurde das Instrument PädKomPflege entwickelt und erprobt. Grundlage des Kompetenzmodells sind die Empfehlungen der Kultusministerkonferenz (2004) zu den Standards für die (allgemeine) Lehrerbildung sowie Expertenworkshops und -interviews mit PflegedidaktikerInnen. Die empirische Erprobung erfolgte an einer Stichprobe von 1096 Pflegelehrpersonen. Psychometrische Analysen auf Grundlage der klassischen Testtheorie sowie IRT-basierte Analysen führten zu einer Überarbeitung des Instruments, welches nun als zweisprachiges Online-Self-Assessmenttool (eng./deut.) vorliegt. Die Validierung der deutschsprachigen Version fand anhand von 545 TeilnehmerInnen im Jahr 2016 statt, sodass ein geprüftes Instrument mit 54 Items in den fünf Hauptskalen (Unterricht, Beurteilung, Beratung, Lernortkooperation sowie Organisations- und Schulentwicklung) und 18 Subskalen zur Verfügung steht. Sowohl klassische als auch probabilistische Testgütekriterien werden erfüllt. Die Skalen weisen hohe interne Konsistenzen auf ( α > 0,80) und sind überwiegend konstruktvalide. So lassen sich für 17 der 18 Subskalen ordinale Raschmodelle anpassen. Auf der Ebene der Hauptskalen können Partial Credit Modelle für alle Items von modellkonformen Subskalen einer Hauptskala angepasst werden. Das Instrument kann zur individuellen Kompetenzdiagnostik, zur Identifikation von Bildungsbedarfen in Schulen des Gesundheitswesens und im Kontext beruflicher Bildungsprozesse genutzt werden. In der Onlineversion erhalten Teilnehmende abschließend ein individuelles Kompetenzprofil mit möglichen Vergleichswerten. Das Tool kann begleitend zu Qualifizierungsprozessen als Monitoring-Instrument oder zur individuellen Kompetenzbilanzierung eingesetzt werden.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology; Developmental and Educational Psychology; Education; Social Psychology

Regulating Transitions from School to Work. An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.
Keywords: Youth; Welfare State; Transitions; Human Service Organizations; Institutional Ethnography; Activation; Sociology of Conventions; Work; Education; Educational Research; Sociology of Education; Social Pedagogy; History of Education; Bielefeld University Press

Regulating Transitions from School to Work. An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.
Keywords: Youth; Welfare State; Transitions; Human Service Organizations; Institutional Ethnography; Activation; Sociology of Conventions; Work; Education; Educational Research; Sociology of Education; Social Pedagogy; History of Education; Bielefeld University Press

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education

Is Reading Comprehension Taken for Granted? An Analysis of Austrian Textbooks in Fourth and Sixth Grade - Seifert, Susanne (Technology, Knowledge and Learning)
Abstract The range of teaching materials now available is becoming increasingly diverse. Despite this, however, the use and influence of textbooks in teaching still remains very high. When instructing reading comprehension, teachers often use textbooks as the basis for teaching in language lessons. Establishing a good match between textbooks and the skills to be acquired is therefore essential. In this paper, I investigate whether textbooks used in Austrian schools can adequately support the teaching of reading comprehension skills. Since reading comprehension is the basis for acquiring knowledge in all subjects, science textbooks are examined in addition to (German) language lesson textbooks. Thus, the content pages of four language textbooks and four science textbooks for fourth and sixth grade were analysed in terms of five different categories, i.e. general structural setup, learning goals, text types, text structures, and activities. The results reveal clear variations with respect to learning goals in language textbooks. For example, the extent to which reading comprehension is addressed ranges from 13.64 to 69.70%, depending on the book used. Although not addressed as a learning goal in the science textbooks, reading comprehension is often presupposed, especially in sixth grade. While the instruction of reading comprehension ought to entail coverage of reading strategies, this is often neglected, or only dealt with indirectly. Given the diversity of textbooks analysed, it seems all the more important to stress that teachers should: 1) clarify the goals and teaching strategies of a book before using it, 2) become aware of strategies that support the development of students' reading comprehension, and 3) use textbooks as a complementary (and not sole) tool to support reading comprehension in all subjects.
Keywords: Computer Science Applications; Human-Computer Interaction; Education; Mathematics (miscellaneous)

The presence of students identified as having special needs as a moderating effect on their classmates’ reading comprehension scores in relation to other major class composition effects - Krammer, Mathias; Seifert, Susanne; Gasteiger-Klicpera, Barbara (Educational Studies)
Keywords: Education

Comparing digital to print assessment of receptive vocabulary with GraWo‐KiGa in Austrian kindergarten - Paleczek, Lisa; Seifert, Susanne; Schöfl, Martin (British Journal of Educational Technology)
Keywords: Education

Teaching and learning in a multilingual Europe: findings from a cross-European study - Dockrell, J. E.; Papadopoulos, T. C.; Mifsud, C. L.; Bourke, L.; Vilageliu, O.; Bešić, E.; Seifert, Susanne; Gasteiger-Klicpera, B.; Ralli, A.; Dimakos, I.; Karpava, S.; Martins, M.; et al. (European Journal of Psychology of Education)
Abstract School classrooms within the EU are multilingual learning environments. The diversity of pupils in classrooms raises significant challenges for teachers, but to date, there are no data from large-scale surveys that compare views within and across European countries. A bespoke questionnaire was designed to examine views of current classroom learning environments with respect to the multilingualism. The questionnaire was piloted and subsequently completed by 2792 teachers across different European countries. Eleven countries provided sufficient data for analyses. Results from structural equation modelling showed that teachers’ attitudes could be reliably measured across Europe with the use of carefully devised questionnaire, whose loading and factor structure remained invariant across countries. Teachers’ views about multilingualism were most challenged by the numbers of children in their classes, not the percentage of multilingual pupils in the class. Countries differed in how they perceived multilingualism, with their differences leading to distinctive country clusters. Gender and education level (elementary vs. secondary) differences were also observed irrespective of country. These findings enhance our understanding of the role that the characteristics of teachers and their classrooms play in a multilingual setting across diverse European settings. The practical relevance of the results and new opportunities for teacher training are discussed.
Keywords: Developmental and Educational Psychology; Education

Increasing the effect of a remedial mathematics course by switching to an online format during the COVID-19 crisis: evidence from a German university - Büchele, Stefan; Liebendörfer, Michael; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Due to the COVID-19 crisis, many courses have been offered digitally. Using data from n = 1,173 business students participating in a preparatory mathematics course at a German university that covered the same content as in 2018, 2019 and 2020, we examine how students’ participation and the effect of the preparatory course changed. The data show that the participation rate has fallen slightly, but students’ participation is rather similar to preceding years. Interestingly, students have participated more intensively. There are clear signs of dishonesty in the self-test (use of a calculator) and significant changes in predictors of performance. In particular, the effect of students’ engagement in the course on their performance substantially increased. Further, we found a gender gap in performance affecting women. Finally, the data show that digital courses can be as effective as on-campus courses.
Keywords: Education; General Mathematics

University students’ fully digital study of mathematics: an identification of student-groups via their resources usage and a characterization by personal and affective characteristics - Kempen, Leander; Liebendörfer, Michael (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract We investigated university students’ study of mathematics in the digital setting context of the COVID-19 pandemic. We gathered data from a survey of 89 students enrolled in a ‘Linear Algebra 1’ course including affective variables, learning strategies, social relatedness and resources considered useful. The results indicate students’ high effort and self-regulation and a high variation in affective characteristics and social relatedness. All the traditional aspects of mathematics teaching (lecture, tutorials and lecture notes) were rated as particularly useful. In addition, the videos from external resources were rated as equally useful as the teaching team’s videos. In contrast, traditional literature such as textbooks was rarely considered useful. The most useful resource rated was communication with peers, underlining the important role of social learning despite fully digital learning environments. Finally, a cluster analysis based on students’ rated usefulness of the resources led to three different user-types. Whereas the ‘digitals’ find the external digital resources very useful (videos, webpages, etc.), the ‘traditionalists’ rate the digitalized traditional resources best (lecture, tutorials, etc.). All resources receive uniformly good ratings from a third group (‘all resource users’). We reflect on our findings in light of the pandemic and describe directions for future research.
Keywords: Education; General Mathematics

Technological and Inclusive Education - Considering Students’ Needs Towards Technological Learning in Primary Schools - Schröer, Franz; Tenberge, Claudia (TECHNE SERIES - Forskning i slöjdpedagogik och slöjdvetenskap)
Research on technological educationininterdisciplinary scienceand socialstudies (Sachunterricht) in German primary schools emphasizes that childrenare generally interested in technology. While several STEAM initiatives point towards a growing recognition of technological literacy, the consideration of technology education ininterdisciplinaryscience and social studies is quite underrepresented in practice as well as in research and teacher training.Takinginto accountthe UN-CRPDclaims foran inclusive educational system andthus alsothe right to equally participate in a free society,participation in society through participation in technological development is a fundamental common goal of technological and inclusive education and part of widely recognized technological literacy.It is therefore not well understood how teaching and learning arrangementscan consider and satisfythe needs of all different students. The research project the present paper is part of tries to unveil the appearance of student’s basic needs in relation to technological educationfor all children. Thisinitial quantitative part of a grounded theory study examined the subjective significance of basic psychological needs in interdisciplinary science studies in primary educationto allow for a well-reasoned sample choice for subsequent interviews. Quantitative results point towards some revisions regarding the instrument used and several implications on the diversity of students ́needs in science and social studies. Future research is needed with larger samples for factor-analysis.
Keywords: Inclusion; basic needs; Technology Education; Primary Education; autonomy; competence; social relatedness

Building, emptying out, or dreaming? Action structures and space in students’ metaphors of academic writing - Scharlau, Ingrid; Karsten, A.; Rohlfing, Katharina J. (Journal of Writing Research)
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics; Education

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils F.; Crawshaw, Camilla E.; Rohlfing, Katharina (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.
Keywords: Education

Academic self-concept, perceptions of inclusion, special needs and gender: Evidence from inclusive classes in Sweden - DeVries, Jeffrey M.; Knickenberg, Margarita; Trygger, Maria (European Journal of Special Needs Education)
Keywords: Developmental and Educational Psychology; Health Professions (miscellaneous); Education